Playfulness and prenatal alcohol exposure: A comparative study - Pearton, Jordan; Ramugondo, Elelwani; Cloete, Lizahn; Cordier, Reinie (Wiley-Blackwell Publishing Asia, 2014)
Background/aim: South Africa carries a high burden of alcohol abuse. The effects of maternal alcohol consumption during pregnancy are most pronounced in poor, rural communities. Earlier research suggests that children with prenatal alcohol exposure have poor social behaviour; however, to date, no research has investigated their playfulness. This study investigated the differences in playfulness of children with and without prenatal alcohol exposure. Methods: Grade one learners with a positive history of prenatal alcohol exposure (n = 15) and a reference group without a positive history of prenatal alcohol exposure (n = 15) were filmed engaging in free play at their schools. The Test of Playfulness was used to measure playfulness from recordings. Data were subjected to Rasch analysis to calculate interval level measure scores for each participant. The overall measure scores and individual Test of Playfulness social items were subjected to paired samples t-tests to calculate if significant differences existed between the groups. Results: Children with prenatal alcohol exposure had a significantly lower mean overall playfulness score than the reference group (t = -2.51; d.f. = 28; P = 0.02). Children with prenatal alcohol exposure also scored significantly lower than the reference group on 5 of the 12 Test of Playfulness items related to social play. Conclusions: This research suggests that children with prenatal alcohol exposure are more likely to experience poorer overall quality of play, with particular deficits in social play. Considering play is a child's primary occupation, this finding becomes pertinent for occupational therapy practice, particularly in post-apartheid South Africa, where high prenatal alcohol exposure prevalence rates are couched within persistent socio-economic inequalities.